Association of dengue virus NS1 protein with lipid rafts - Noisakran S. (2014)
During the replication of dengue virus, a viral non-structural glycoprotein, NS1, associates with the membrane on the cell surface and in the RNA replication complex. NS1 lacks a transmembrane domain, and the mechanism by which it associates with the membrane remains unclear. This study aimed to investigate whether membrane-bound NS1 is present in lipid rafts in dengue virus-infected cells. Double immunofluorescence staining of infected HEK-293T cells revealed that NS1 localized with raft-associated molecules, ganglioside GM1 and CD55, on the cell surface. In a flotation gradient centrifugation assay, a small proportion of NS1 in Triton X-100 cell lysate consistently co-fractionated with raft markers. Association of NS1 with lipid rafts was detected for all four dengue serotypes, as well as for Japanese encephalitis virus. Analysis of recombinant NS1 forms showed that glycosylated NS1 dimers stably expressed in HEK-293T cells without an additional C-terminal sequence, or with a heterologous transmembrane domain, failed to associate with lipid rafts. In contrast, glycosylphosphatidylinositol-linked recombinant NS1 exhibited a predilection for lipid rafts. These results indicate an association of a minor subpopulation of NS1 with lipid rafts during dengue virus infection and suggest that modification of NS1, possibly lipidation, is required for raft association. © 2008 SGM.